Do tuberculosis treatment supporters influence patients treatment outcome? A study in the southern service delivery region, Ekurhuleni Metropolitan Municipality, Gauteng Province, South Africa - Oduor, Peter Aggrey (My University, 2008)
Abstract This study aimed to investigate the role played by treatment supporters in promoting patients’ treatment outcomes in six TB clinics of Ekurhuleni Metropolitan Municipality, Gauteng. A descriptive research design was used to study TB patients who were registered in the clinics in April and May 2006. Interviews were conducted on 216 new adult patients six months after their registration at clinics, all 30 treatment supporters of those who had supporters and the staff responsible for TB at the six clinics at which the patients were registered. The patients were grouped into those who had supporters 53% (n=115) and those who did not 47% (n=101). Patients’ response rate was 97%. Treatment outcomes were compared between these two groups. Results showed that significantly more supported patients achieved successful outcomes than patients who did not have supporters. The results did not change when transfers and deaths were excluded from the measurement. Successful treatment outcomes were significantly associated with treatment supporters having fewer than 10 patients, patients living with someone, patients of age 40 or more years, male patients, those whose highest education levels were tertiary and secondary. Patients and clinic staff said that supporters were useful in checking on patients’ treatment, giving medicine, counselling and advising patients on medication and in practical help. Conclusion: Treatment supporters had a significant role in promoting patients’ treatment outcomes. It is recommended that TB treatment programme staff should consider using treatment supporters in their programmes.
Keywords: tuberculosis; Ekurhuleni; treatment supporters; treatment outcome